THE EFFECT OF AUDIT TENURE, AUDIT ROTATION, FIRM SIZE AND AUDIT COMMITTEES ON AUDIT QUALITY WITH SPECIALIST AUDITORS AS MODERATORS IN REAL ESTATE & PROPERTY COMPANIES IN 2013-2018 - Zuhroh, Shufia (Asosiasi Dosen Akuntansi Indonesia, 2020)
This study aims to determine and analyze the effect of audit tenure, audit rotation, firm size and audit committee on audit quality with specialist auditors as moderating real estate & property companies listed on the Indonesia Stock Exchange. The results of this study prove that audit tenure has a negative and not significant effect on audit quality, while audit rotation has a negative and significant effect on audit quality, firm size has a positive and not significant effect on audit quality and audit committee has a positive and significant effect on audit quality. Specialist Auditors are not significant in moderating the effect of audit tenure, audit rotation, firm size and audit committee on audit quality.